Pengaruh budaya organisasi dan motivasi kerja terhadap kinerja staff BAPPEDA Kabupaten. Bima - Alfiansyah, Alfiansyah; Badar, Badar; Yusuf, Yusuf (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2023)
The purpose of this research is to find out whether organizational culture has a significant effect on staff performance at the Bima Regency Bappeda office, to find out whether work motivation has a significant effect on staff performance at the Bima Regency Bappeda office, to find out whether organizational culture and work motivation have a significant effect on performance. Bima Regency Bappeda office staff, In this study the population was 111 people consisting of: Civil Servants (PNS) = 65 people, Main Support Staff = 13 people and Voluntary Employees = 33 people, and the number of samples in this study was as many as 52 respondents. The data collection techniques used were literature study, documentation and questionnaires. This research was conducted at the Bima Regency Bappeda office. JL Gatot Soebroto, No. 02, Raba, Monggonao, District. Mpunda, Kota. Bima, West Nusa Tenggara (NTB) 84113. Data analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression test, T test and F test The results of the research show that there is a significant influence between Organizational Culture on Employee Performance at the Bima Regency Regional Development Planning Agency (BAPPEDA), there is no significant influence between Work Motivation on Staff Performance at the Bima Regency Regional Development Planning Agency (BAPPEDA) and there is a significant influence simultaneous between Organizational Culture and Work Motivation on Staff Performance at the Regional Development Planning Agency (BAPPEDA) of Bima Regency.